Unveiling the effect of molybdenum and titanium co-doping on degradation and electrochemical performance in Ni-rich cathodes - Imesha Rambukwella; Konstantin L. Firestein; Yanan Xu; Ziqi Sun; Shanqing Zhang; Cheng Yan (Materials Reports: Energy)
In this work, we have applied molybdenum (Mo) and titanium (Ti) co-doping to solve the degradation of Ni-rich cathodes. The modified cathode, i.e., Li(Ni0.89Co0.05Mn0.05Mo0.005Ti0.005)O2 holds a stable structure with expanded crystal lattice distance which improves Li ion diffusion kinetics. The dopants have suppressed the growth of primary particles, formed a coating on the surface, and promoted the elongated morphology. Moreover, the mechanical strength of these particles has increased, as confirmed by the nanoindentation test, which can help suppress particle cracking. The detrimental H2-H3 phase transition has been postponed by 90 mV allowing the cathode to operate at a higher voltage. A better cycling stability over 100 cycles with 69% capacity retention has been observed. We believe this work points out a way to improve the cycling performance, Coulombic efficiency and capacity retention in Ni-rich cathodes.